Monetizing Smart ADT Systems: A Digital Business Model for Traffic-as-a-Service (TaaS) - Louisa Arthur Limantara; Nanang Hoesen Hidroes Abbrori; Arthur Daniel Limantara (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2026)
Traffic congestion remains a persistent problem in mid-sized Indonesian cities, including Kediri, where several key intersections experience recurrent bottlenecks. Average Daily Traffic (ADT) monitoring has traditionally relied on manual counts, which are prone to inaccuracies and lack sustainability. This study examines the integration of Smart ADT systems with Internet of Things (IoT) sensors, edge computing, and cloud-based analytics to develop a Traffic-as-a-Service (TaaS) model for Kediri. Using a traffic-survey model derived from municipal planning discussions, this research highlights the technical and business feasibility of TaaS. Findings from the Kediri pilot indicate recurring congestion during peak commuting hours, with IoT-enabled monitoring providing real-time data to support predictive traffic management. Monetization opportunities include government subscriptions, shared-use platforms for multi-agency data, and integration with logistics and mobility services. The study underlines that sustainable financing and robust data governance are prerequisites for scaling TaaS in Indonesian secondary cities.